Effects of particle size on the crystallization kinetics characterization in CaO-SiO2-based glass, part 1: in a simple crystallization process with only one crystal phase - Zhen Wang; Renze Xu (Journal of Asian Ceramic Societies)
In-depth research on the influencing mechanisms of particle size on the crystallization of silicate glass were conducted by calculating the crystallization kinetic parameters using exothermic peaks in differential thermal analysis curves and the Matusita-Sakka equation. A typical silicate glass, CaO-SiO2-B2O3, with a simple crystallization process that forms only one crystal (CaSiO3) was selected as the vehicle for this study. For the as-quenched glass sample, as the particle size distribution shifted from 2.5–1 mm to less than 0.061 mm, the crystal growth dimensionality shifted from a two- to a three-dimensional mechanism. The turning point of the particle size corresponding to the change in crystal growth dimensionality is defined as the boundary between fine and coarse particles and was found to be 0.104 mm. With decreasing particle size, the activation energy for crystal growth decreased slightly in the fine-particle starting material and increased in the coarse-particle starting material; the decrease being considerably higher than the increase. Although the as-quenched glass comprising fine particles is regarded to have saturated nucleation sites, as in the case of well-nucleated samples, it exhibited different crystal growth mechanisms because of its different nucleation mechanisms.